(untitled) (Revista de Medicina Clinica, 2022)
Background: Evans syndrome is a rare chronic hematologic condition with a worldwide incidence of 1.8 per million population per year. It is characterized by the presence of two or more cytopenias, including autoimmune hemolytic anemia (AIHA) and idiopathic thrombocytopenic purpura (ITP). Diagnosis is challenging as it is made by exclusion of other infectious, malignant, or autoimmune diseases. Clinical presentation is induced directly by the anemia and thrombocytopenia. Case report: 22-year-old male patient diagnosed with thrombocytopenia, presenting with nonspecific, repetitive, and self-limited symptoms for 3 years. He presented episodes of epistaxis, gingivorrhage, headache with photosensitivity, and hemorrhoids. With associated ecchymosis and petechiae in extremities and oral mucosa, as well as splenomegaly. Laboratory results report hemoglobin of 11.6 g/dL, platelets of 3,000/mm3 and positive direct Coombs test. The patient was ultimately diagnosed with Evans syndrome and hospitalized for plasmapheresis and steroids administration. He is reported stable. Conclusions: Evans syndrome may have remissions and exacerbations during the person´s lifetime, but it has a favorable prognosis with appropriate treatment and early recognition, so it must be an important differential diagnosis in patients with hemolytic anemia, positive Coombs, and autoimmune thrombocytopenia.